Advanced point-of-care biomarker testing for the diagnosis of cardiovascular diseases - Wenjun Ming; Yidan Zhu; Wenjun Jiang; Jing Zhang; Jinxia Liu; Li Wu; Yuling Qin (Sensing and Bio-Sensing Research)
Cardiovascular disease (CVD) stands as the primary cause of global mortality, necessitating early diagnosis for mitigating death rates and improving quality of life. Conventional CVD diagnostic techniques necessitate the use of bulky hospital instruments for electrocardiogram recording and immunoassay, resulting in time-consuming and inconvenient limitations. Point-of-care testing (POCT) presents unique benefits compared to traditional central laboratory (CLT) methods, such as accelerated turnaround times for results, enhanced portability, and ease of use, which are especially beneficial in resource-constrained healthcare environments. As a result, POCT is increasingly recognized as an innovative diagnostic strategy for the management of CVD, achieving significant standing across a variety of healthcare scenarios. The present review offers a comprehensive overview of the prevailing categories of cardiovascular diseases and emphasizes the diagnostic application of cardiac biomarkers detected through blood tests. The focus of this study is specifically on POCT devices used for the detection of biomarkers related to cardiovascular disease. Additionally, their performance will be compared and evaluated against traditional CLT methods and commercially available equipment. With the growing implementation of hierarchical medical policies and increasing demand for health management services, the market for POCT cardiac biomarkers testing is expected to expand further as a crucial development direction within the field of medicine.